Digital consumer management : understanding and managing consumer engagement in the digital environment - Mogaji, Emmanuel (New York, NY : Routledge, 2024)
"Integrating consumer behaviour, digital marketing, digital platform management, web analytics and marketing insights, Digital Consumer Management provides a holistic understanding - from a brand perspective - of the management of consumers and consumption in the digital ecosystem. Chapters explore the key stakeholders in platform management, the multiple types of platforms used by brands, the various consumer-brand touchpoints, how the platforms are developed and with what goals in mind, managing consumer engagement and activities on these platforms, how the platforms are regulated, and the dark side of digital consumption. Theory is brought to life by practical examples and case studies from across sectors, and reflective questions and activities allow students to critically reflect on their learning. Providing a comprehensive picture of digital consumption activities, digital consumer behaviour across platforms, and how brands can manage and engage with the digital consumer, this text works as core and recommended reading for students studying digital consumer behaviour, digital marketing and marketing management. Accompanying online resources include PowerPoint slides and an instructor's manual"--Provided by publisher.
Includes bibliographical references.
Keywords: Information technology -- Management; Technological innovations -- Management; Industrial management -- Data processing